Community Based Breastfeeding Counseling for Succesfull Exclusive Breastfeeding - Dwi Rahayu; Yunarsih Yunarsih (Universitas STRADA Indonesia, 2019)
Maternal problems during the postpartum are physiological and psychological changes. The postpartum period is a critical moment to adapt stress after childbirth. Adaptations include adjusting to the partner and building positive interactions with the baby. One of the problems that occurred during the postpartum period is fail in giving exclusive breastfeeding. The purpose of this study is to prove the influence of Community Based Breastfeeding Counseling for successfull exclusive breastfeeding.The research design used pre experimental design with one group pre-post test design approach. The respondents are Pospartum Primipara. Data collection with questionnaire sheets for the success of Exclusive Breastfeeding. Data analysis using Chi-Square with significance level α = 0.05 obtained result x2 = 0,000 and coefficient contingency = 0.707 means there is a difference between Practice of exclusive breastfeeding before and after done Community Based Breastfeeding Counseling means there is influence of Community Based Breastfeeding Counseling for Successful Exclusive breastfeeding